2021
DOI: 10.3390/atmos12020130
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Exposure from Airborne Hazardous Short-Duration Releases in Urban Environments

Abstract: When considering accidental or/and deliberate releases of airborne hazardous substances the release duration is often short and in most cases not precisely known. The downstream exposure in those cases is stochastic due to ambient turbulence and strongly dependent on the release duration. Depending on the adopted modelling approach, a relatively large number of dispersion simulations may be required to assess exposure and its statistical behaviour. The present study introduces a novel approach aiming to replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The use of time-integrated measurements excludes the influence of the correctness of the plume arrival time on the value of cost function (1). It should be noted that, in the case of stationary meteorology, the use of time-integrated observations is fully justified mathematically: it could be shown that, in stationary meteorological conditions, time-integrated concentrations following a finite duration release are proportional to concentrations following a continuous release with a proportionality constant independent of sensor's location [26].…”
Section: Assessment Of Source Locationmentioning
confidence: 99%
“…The use of time-integrated measurements excludes the influence of the correctness of the plume arrival time on the value of cost function (1). It should be noted that, in the case of stationary meteorology, the use of time-integrated observations is fully justified mathematically: it could be shown that, in stationary meteorological conditions, time-integrated concentrations following a finite duration release are proportional to concentrations following a continuous release with a proportionality constant independent of sensor's location [26].…”
Section: Assessment Of Source Locationmentioning
confidence: 99%